The Effect of the Use of Collaborative Educational Supervision on Increasing Lecturer Performance in Online Learning - Ari Lestari (Jurnal Mantik, 2022)
Based on article 20 of the Law on Teachers and Lecturers, it is explained that in carrying out professional duties, there are several obligations that must be fulfilled, namely planning, implementing and assessing and evaluating learning, improving and developing qualifications and competencies, having objective actions, upholding the rules that have been outlined and maintaining and foster a sense of national unity and integrity. One of the indicators of success in improving the quality of education is that the learning process is not just about imparting knowledge, but is more focused on internalizing the development of cognitive, affective and psychomotor aspects as well as bathing. Then the collaborative education supervision is carried out periodically and gradually which will result in an improvement in learning which can be achieved by measuring the value obtained by students in one unit such as a semester or department. In general, the use of collaborative supervision has an influence on performance by looking for forms or methods or learning strategies that are in accordance with the majors taken by students.